Verbal humor created by flouting maxims in how i met your mother series - Aritorang, Athalia Beshorah; Beratha, Ni Luh Sutjiati; Sukarini, Ni Wayan (Aksara: Jurnal Bahasa dan Sastra, 2023)
This article is entitled Humorous Situation Created by Flouting of Maxim in Comedy Series How I Met Your Mother. It is aimed at identifying the types of maxims being used in order to create verbal humor. The data was taken from “How I Met Your Mother” comedy series. This undergraduate thesis applied two theories to solve the problems. The first is the theory is the Grice’s maxims to identify what are the maxims flouted in the series and also to find which maxim is dominantly flouted. Whereas, the second theory is the theory of verbal humor by Shade. This undergraduate thesis used the documentation method for collecting data, the data was collected from the comedy series by watching the series, reading the movie script as well as seen at the subtitle of the series. Then identify the maxims flouted by the characters in it. The result of this undergraduate thesis shows that all maxims were flouted in the series. And there were four types of verbal humor implied in the series How I Met Your Mother.